Analisis Gaya Kepemimpinan dan Motivasi Kerja dalam Meningkatkan Disiplin Kerja Guru di Madrasah Tsanawiah (MTs) Al- Ihsan Kalikejambon - Lailatus Sa’adah; Septian Ragil Anandita; Zawaidul Khair (Sekolah Tinggi Ilmu Administrasi Yappi Makassar, 2024)
This study aims to analyze leadership styles and working motivation in improving teacher work discipline in Madrasah Tsanawiah (Mts) Al-Ihsan Kalikejambon. The research method used a qualitative method with data collection observation, interviews and documentation involving directly to the principal headmaster and teachers of Madrasah Tsanawiah (Mts) Al-Ihsan Kalikejambon. Data analysis techniques include data reduction, data presentation and conclusion drawing. The results of this study indicate that in improving teacher work discipline in Madrasah Tsanawiah (Mts) Al-Ihsan Kalikejambon, the principal applies a democratic leadership style and intrinsic and extrinsic motivation.